Proses Morfologi Basa Bali Pada Buku Ajar Bahasa Bali Pangkaja Sari SMP Kelas IX - Trisna Suryantari, Ni Kadek (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This study discusses the morphological process of Balinese words in the Pangkaja Sari Balinese language textbook for Class IX Middle School. The purpose of this research is to reveal the linguistic aspects in the textbooks of Pangkaja Sari SMP Class IX, especially from the morphological processes including affixation, reduplication, and composition. The source of the data for this research is the Balinese Pangkaja Sari textbook for SMP Class IX. The theory used is the theory of structural linguistics. This research belongs to the type of qualitative research. The data collection method used is observation and literature. The data analysis used data reduction, data presentation and conclusion drawing. Based on the research conducted, it is known that in the Balinese language textbook Pangkaja Sari SMP Class IX found the morphological processes of the Balinese language including the processes of affixation, reduplication and composition. The results showed that (1) The morphological processes of Balinese words in the Balinese language textbook Pangkaja Sari SMP Class IX are: Affixation includes the addition of prefixes N-, ma-, ka-, pa- , sa-; addition of suffixes -a, -ang, -in, -an, -é, -né, -n and -ing; addition of -in- and -um- infixes; addition of confixes pa-an, ka-an, and ma-an; affix combination N-ang. Reduplication includes pure repeat words, sound change words, pseudo repeats and dwipurwa repeats. The composition process consists of equivalent compound words, unequal compound words and compound words with unique elements.